Gods, goddesses, and the women who serve them - Ackerman, Susan (William B. Eerdmans Publishing Company, 2022)
"A collection of scholarly works on women in ancient Israelite religion, with subjects including the worship of goddesses, the roles women played as religious functionaries, and the Hebrew Bible's accounts of women's religious lives"--